Deconvolution of Adult T-Cell Leukemia/Lymphoma With Single-Cell RNA-Seq Using Frozen Archived Skin Tissue Reveals New Subset of Cancer-Associated Fibroblast - Joo, Eun-Hye; Bae, Jai Hee; Park, Jihye; Bang, Yoon Ji; Han, Joseph; Gulati, Nicholas; Kim, Jong-Il; Park, Chung-Gyu; Park, Woong-Yang; Kim, Hyun Je (Frontiers in Immunology, 2022)
Adult T-cell Leukemia/Lymphoma (ATLL) is a rare aggressive T-cell malignancy associated with human T-cell leukemia virus type 1 (HTLV-1) infection. However, little is known about the underlying activated molecular pathways at the single cell level. Moreover, the intercellular communications between the tumor microenvironment (TME) and tumor cells in this malignancy are currently unknown. Difficulties in harvesting fresh tissue in a clinical setting has hampered our deeper understanding of this malignancy. Herein, we examined ATLL using archived fresh frozen tissue after the biopsy by single-cell RNA sequencing (scRNA-seq) with T-cell receptor (TCR) clonal analysis. Highly clonal tumor cells showed multiple activating pathways, suggesting dynamic evolution of the malignancy. Dissecting diverse cell types comprising the TME led to the identification of a novel subset of cancer-associated fibroblast which showed enriched epidermal growth factor receptor (EGFR)-related transcripts. These findings suggest a potential targeted therapeutic pathway to better treat this neoplasm.